Scalable Production of Human Mesenchymal Stromal Cell-Derived Extracellular Vesicles Under Serum-/Xeno-Free Conditions in a Microcarrier-Based Bioreactor Culture System - de Almeida Fuzeta, Miguel; Bernardes, Nuno; Oliveira, Filipa D.; Costa, Ana Catarina; Fernandes-Platzgummer, Ana; Farinha, José Paulo; Rodrigues, Carlos A. V.; Jung, Sunghoon; Tseng, Rong-Jeng; Milligan, William; Lee, Brian; Castanho, Miguel A. R. B.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stromal cells (MSC) hold great promise for tissue engineering and cell-based therapies due to their multilineage differentiation potential and intrinsic immunomodulatory and trophic activities. Over the past years, increasing evidence has proposed extracellular vesicles (EVs) as mediators of many of the MSC-associated therapeutic features. EVs have emerged as mediators of intercellular communication, being associated with multiple physiological processes, but also in the pathogenesis of several diseases. EVs are derived from cell membranes, allowing high biocompatibility to target cells, while their small size makes them ideal candidates to cross biological barriers. Despite the promising potential of EVs for therapeutic applications, robust manufacturing processes that would increase the consistency and scalability of EV production are still lacking. In this work, EVs were produced by MSC isolated from different human tissue sources (bone marrow (BM), adipose tissue (AT) and umbilical cord matrix (UCM)). A serum-/xeno-free microcarrier-based culture system was implemented in a Vertical-Wheel™ bioreactor (VWBR), employing a human platelet lysate culture supplement (UltraGRO™-PURE), towards the scalable production of MSC-derived EVs (MSC-EVs). The morphology and structure of the manufactured EVs were assessed by atomic force microscopy, while EV protein markers were successfully identified in EVs by Western blot, and EV surface charge was maintained relatively constant (between -15.5 ± 1.6 mV and - 19.4 ± 1.4 mV), as determined by zeta potential measurements. When compared to traditional culture systems under static conditions (T-flasks), the VWBR system allowed the production of EVs at higher concentration (i.e. EV concentration in the conditioned medium) (5.7-fold increase overall) and productivity (i.e. amount of EVs generated per cell) (3-fold increase overall). BM, AT and UCM MSC cultured in the VWBR system yielded an average of 2.8 ± 0.1 x 10^11, 3.1 ± 1.3 x 10^11 and 4.1 ± 1.7 x 10^11 EV particles (n=3), respectively, in a 60 mL final volume. This bioreactor system also allowed to obtain a more robust MSC-EV production, regarding their purity, compared to static culture. Overall, we demonstrate that this scalable culture system can robustly manufacture EVs from MSC derived from different tissue sources, towards the development of novel therapeutic products.